2020
DOI: 10.1016/j.fishres.2020.105671
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the survival of discarded Nephrops norvegicus in a NW Mediterranean bottom-trawl fishery

Abstract: The landing obligation in the revised European Union Common Fisheries Policy allows for exemptions to obligatory landing of the entire catch for species for which "high survival" of discards can be demonstrated. Nephrops norvegicus is an important target species in many fisheries across Europe in the Mediterranean Sea, NE Atlantic Ocean and North Sea. Historically, Mediterranean fisheries have had a high discard rate of small-sized Nephrops, and it is suspected that this unwanted component of the catch may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Improvements in onboard vitality in N. norvegicus treated with cool water may be due to a reduction in stress that is accompanied by a recovery in plasma values and muscle metabolites such as lactate found in non-stressful conditions, although the only study carried out in this regard had a longer duration (Barragán-Mendez et al 2020). For the implementation of this new discard-handling method, it should be taken into account that trawlers in the Mediterranean usually carry out several hauls during the fishing day (Demestre et al 2018, García-de-Vinuesa et al 2020. For this reason, after their arrival on board, the catch remains on the deck waiting for the crew members to finish carrying out the manoeuvre of shooting the trawl net to start the next haul, which usually takes at least 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in onboard vitality in N. norvegicus treated with cool water may be due to a reduction in stress that is accompanied by a recovery in plasma values and muscle metabolites such as lactate found in non-stressful conditions, although the only study carried out in this regard had a longer duration (Barragán-Mendez et al 2020). For the implementation of this new discard-handling method, it should be taken into account that trawlers in the Mediterranean usually carry out several hauls during the fishing day (Demestre et al 2018, García-de-Vinuesa et al 2020. For this reason, after their arrival on board, the catch remains on the deck waiting for the crew members to finish carrying out the manoeuvre of shooting the trawl net to start the next haul, which usually takes at least 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…This refrigeration can be carried out by simple means such as contact with the ice in the container (all trawlers carry ice compulsorily to keep the commercial catch cool for sale) well in advance until the manoeuvres are finished. This practice would improve the post-release survival of trawling of N. norvegicus, especially during the warm months, when their mortality has been shown to be higher both in the Mediterranean and in the Atlantic (Méhault et al 2016, García-de-Vinuesa et al 2020, Fox et al 2020. In this trawl fishery, the amount of catches under the MCRS is very low (ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its importance and high economic value as a commercial species in the Atlantic and North Sea [2,3,9], Nephrops has been the subject of several biological and fishery studies , leading to the collection of long time series data for that region. In regard to the Mediterranean Sea, most of the studies have focused on the Western region and the Adriatic sea [7,8,13,15,[30][31][32][33][34][35][36][37][38], with the majority of them within the framework of the EU research project "MEDITS" [39], contrary to even fewer studies in the Eastern Mediterranean and the Aegean Sea [40][41][42][43][44]. The aim of the present study was to fill that knowledge gap in the Eastern Mediterranean, since no such studies were found for the region.…”
Section: Introductionmentioning
confidence: 95%
“…However, not all species are affected in the same way. Some may be more vulnerable and others may be more resilient (Dimech et al 2012, García de Vinuesa et al 2020. Additionally, some of them may be key species for the proper functioning of the ecosystem.…”
Section: Introductionmentioning
confidence: 99%